2014
DOI: 10.1155/2014/313867
|View full text |Cite
|
Sign up to set email alerts
|

Rural Residents in China Are at Increased Risk of Exposure to Tick-Borne PathogensAnaplasma phagocytophilumandEhrlichia chaffeensis

Abstract: As emerging tick born rickettsial diseases caused by A. phagocytophilum and E. chaffeensis, anaplasmosis and ehrlichiosis have become a serious threat to human and animal health throughout the world. In particular, in China, an unusual transmission of nosocomial cases of human granulocytic anaplasmosis occurred in Anhui Province in 2006 and more recent coinfection case of A. phagocytophilum and E. chaffeensis was documented in Shandong Province. Although the seroprevalence of human granulocytic anaplasmosis (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 29 publications
0
29
1
Order By: Relevance
“…In these studies, the infection rates at different sampling sites varied from 0 to 78.1%, which implies an extensive distribution of this pathogen in China (22). The prevalence of A. phagocytophilum infection in sheep and goats in the regions surveyed in the current study was lower than in sheep and goats from Gansu Province (40.0%, 56/140) and central and Southeastern China (25.2%, 106/421), but higher than in goats from Henan (13.0%, 6/46), Jilin (5.7%, 8/35), and Hubei (14.5%, 10/69) (23). This may have been due to the sampling sites chosen, temporal effects on samples, the sampling method used, the distribution of the vectors, the different diagnostic methods used, or any other factor related to the ecological environment.…”
Section: Resultscontrasting
confidence: 55%
“…In these studies, the infection rates at different sampling sites varied from 0 to 78.1%, which implies an extensive distribution of this pathogen in China (22). The prevalence of A. phagocytophilum infection in sheep and goats in the regions surveyed in the current study was lower than in sheep and goats from Gansu Province (40.0%, 56/140) and central and Southeastern China (25.2%, 106/421), but higher than in goats from Henan (13.0%, 6/46), Jilin (5.7%, 8/35), and Hubei (14.5%, 10/69) (23). This may have been due to the sampling sites chosen, temporal effects on samples, the sampling method used, the distribution of the vectors, the different diagnostic methods used, or any other factor related to the ecological environment.…”
Section: Resultscontrasting
confidence: 55%
“…First, with the advancement of China’s urbanization process and the expansion of enrollment in higher education institutions, a large number of middle-aged men and young people from rural areas have entered the city to work or study, and the elderly become the main force of agricultural production[34]. Therefore, elder people who had more opportunity to expose to insect vector when undertaking farm work than young people who work or study in cities except Spring Festival[35]. Second, the immune function of the elderly may be lower than young people.…”
Section: Discussionmentioning
confidence: 99%
“…In China, 46 confirmed and 16 probable cases were diagnosed from 2009 to 2010 with an 8.1% fatality rate (Zhang et al, 2013). However, seroprevalence studies suggest that the number of reported cases in China is underestimated (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%